Peer Group Education and Healthy Snacking for Adolescent Girls (Prospective Mothers) in Islamic Boarding Schools as an Effort to Reduce the Number of Stunting Cases - Wimar Anugrah Romadhon; Ning Arti Wulandari; Nur Aini Mahmudah (STIKes Patria Husada Blitar, 2025)
Young women, as prospective mothers, needed to prepare themselves to give birth to a quality generation. Preventing stunting in adolescents involved increasing knowledge and awareness of the use of local foods. The partner in this community service program was the Madrosatul Qur'an Hidayatul Mubtadiin Islamic Boarding School. The goal of this community service program for beginners was to increase the knowledge and awareness of young women (prospective mothers) at the Islamic boarding school regarding the importance of balanced nutrition for stunting prevention from adolescence, encourage healthy snacking habits based on local foods, increase access to nutritious food to support healthy nutrition for adolescents as a stunting prevention effort, and develop adolescent health cadres capable of becoming agents of change within the Islamic boarding school and the surrounding community. The results of data analysis using the Wilcoxon signed rank test obtained P = 0.000, so it was concluded that the provision of peer group education could increase the knowledge and awareness of young women (prospective mothers) regarding the importance of balanced nutrition for preventing stunting since adolescence and that was achieved was that the students exhibited very good healthy snacking behavior (88%) and fairly good healthy snacking behavior (12%). This service encouraged healthy snacking habits to fulfil balanced nutrition for students, increased access to nutritious food to support nutritional fulfillment as an effort to prevent stunting by modifying a healthy canteen, and built health cadres of adolescent cadres who were able to become agents of change in the community.